First report of putative Leishmania RNA virus 2 (LRV2) in Leishmania infantum strains from canine and human visceral leishmaniasis cases in the southeast of Brazil - Rêgo, Felipe Dutra; da Silva, Eduardo Sérgio; Lopes, Valeriana Valadares; Teixeira-Neto, Rafael Gonçalves; Belo, Vinícius Silva; Fonseca Júnior, Antônio Augusto; Pereira, Diego Andrade; Pena, Heber Paulino; Laurenti, Márcia Dalastra; Araújo, Gabriela V; da Matta, Vânia Lúcia Ribeiro; Chouman, Islam Hussein; et al. (Memorias do Instituto Oswaldo Cruz, 2023)
BACKGROUND: Leishmania RNA virus 1 (LRV1) is commonly found in South American Leishmania parasites belonging to the subgenus Viannia, whereas Leishmania RNA virus 2 (LRV2) was previously thought to be restricted to the Old-World pathogens of the subgenus Leishmania. OBJECTIVES: In this study, we investigated the presence of LRV2 in strains of Leishmania (L.) infantum, the causative agent of visceral leishmaniasis (VL), originating from different hosts, clinical forms, and geographical regions. METHODS: A total of seventy-one isolates were screened for LRV2 using semi-nested reverse transcription-polymerase chain reaction (RT-PCR) targeting the RNA-dependent RNA polymerase (RdRp) gene. FINDINGS: We detected LRV2 in two L. infantum isolates (CUR268 and HP-EMO) from canine and human cases, respectively. MAIN CONCLUSIONS: To the best of our knowledge, this is the first detection of LRV2 in the New World.
Keywords: Dogs; leishmanióza viscerální; Animals; Leishmania infantum; lidé; RNA-dependentní RNA-polymerasa; Brazílie; Leishmaniasis, Visceral; Brazil; RNA-Dependent RNA Polymerase; Humans; zvířata; psi